Modeling the energy potential of the Toktogul hydroelectric power station (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper focuses on modeling the energy potential of the Toktogul Hydroelectric Power Plant (HPP), the largest hydropower facility in Kyrgyzstan. The main objective of the study is to quantitatively assess the station’s power generation capacity and annual energy output under varying climatic and hydrological conditions. The modeling approach is based on the classical physical equation P=η⋅ρ⋅g⋅Q⋅H implemented as a computational model in the Python programming environment. Real hydrometeorological data—including water discharge, reservoir head, temperature, and precipitation—were integrated in CSV format for monthly and annual energy calculations. Climate scenario simulations showed that an increase in temperature by +3 °C decreases power output by approximately 7%, while a 20% rise in precipitation increases it by about 5%. An interactive web-based model developed using the Streamlit platform enables real-time parameter adjustments and visualization of the hydropower potential. The obtained results demonstrate the practical applicability of the proposed model for optimizing the operation of the Toktogul HPP and for developing adaptive strategies in Kyrgyzstan’s energy sector in response to climate change.
Keywords: Toktogul Hydropower Plant, energy potential, hydropower, mathematical modeling, climate scenarios, hydrometeorological data, optimization of Kyrgyzstan’s energy system